Clarifying Organizational Requirements through Rapid Application Development: Evidence from a Performance Appraisal Information System - Handy Setiawan; Koko Wahyu Prasetyo (J-INTECH ( Journal of Information and Technology), 2026)
This study analyzes the iterative application of Rapid Application Development (RAD) in the engineering of an employee performance appraisal information system within a higher education context. The system was developed to replace a spreadsheet-based process that involved manual score aggregation and fragmented data storage. Using a software engineering case study approach, this research examines how system requirements evolved across development iterations. Design artifacts produced during successive RAD cycles were analyzed as evidence of requirement refinement. The findings show that early development focused on functional centralization, while later iterations introduced configurable modules for evaluation criteria, evaluator assignment, and score normalization. These interface and module revisions reflect progressive clarification of organizational needs and stabilization of business logic. The study demonstrates that RAD supports requirement refinement through iterative prototyping, especially in systems involving multiple roles and configurable structures. The results provide process-oriented insight into requirement evolution in internal organizational information systems.